Macroeconomic Factors and Stock Market Performance in Pakistan: An Empirical Investigation Using ARDL and NARDL Models - Farooq, Mehdi (2020)
Objective: The purpose of this study was to examine how macroeconomic variables impact stock performance in the long-run and the short-run of Pakistan. It also inspected whether the impact of macroeconomic variables on stock performance had a symmetric or asymmetric effect. Methodology: This study used autoregressive distributed lag models (ARDL) in linear and non-linear forms to empirically investigate the effects of the exchange rate, interest rate, inflation, VIX, and real GDP on the stock market performance of Pakistan. The researcher used annual time series data covering the period 1991-2020. Results: Empirical results reveal apart from the real GDP growth rate; all the other macro variables had a statistically significant impact on Pakistan’s equity performance in both the short and long run. Error Correction Model pointed out the rapid market pricing of macro shocks. Lastly, NARDL proved that excluding interest rate, all variables under consideration had a symmetrical impact on stock prices in the long run. Policy implications: The study recommends that in order for the monetary authorities to stimulate the stock market, bank lending rates should be kept accommodative. The State Bank of Pakistan, to negate the short-run impact of depreciation, should not unnecessarily utilise their FX reserves to support stock markets as in the long run, depreciation tends to boast equity performance; and any intervention will delay the stabilisation. To combat global macro shocks, targeted capital controls, policy coordination with global central banks, and macroprudential interventions are recommended. Originality: This would be the first study to examine the impact of VIX on Pakistan equities. Similarly, domestic literature has not considered non-linearity when investigating the impact of macro shocks on Pakistan stock returns, and this study will fill in the gap. Keywords: Asymmetry, ARDL, Macroeconomic Shocks, NARDL, PSX-100, Stock Performance, VIX